How do you solve \[4{{x}^{2}}+5x-6=0\] using the quadratic formula?
Answer
Verified
444k+ views
Hint: For answering this question we are asked to solve the given equation \[4{{x}^{2}}+5x-6=0\] and find the value of the variable $x$ . For solving that we will make some transformations like shifting from right hand to left hand side and vice versa and basic arithmetic simplifications like addition and subtraction then we need to conclude the value of the unknown variable $x$ .
Complete step-by-step answer:
Now considering the question in which we are asked to solve the given equation \[4{{x}^{2}}+5x-6=0\] and derive the value of the unknown variable \[x\].
Firstly, we will observe the given equation carefully and compare the given quadratic equation with the basic quadratic equation \[a{{x}^{2}}+bx+c=0\].
By comparing the given quadratic equation \[4{{x}^{2}}+5x-6=0\] with the basic quadratic equation \[a{{x}^{2}}+bx+c=0\] , we get,
\[\Rightarrow a=4,b=5,c=-6\]
Here in the question the variable x is nothing but the roots of the given equation \[4{{x}^{2}}+5x-6=0\] .
We can find the roots of the quadratic equation by basic formula \[x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}\] . After comparing the given quadratic equation with the basic equation we substitute them and we get,
\[\Rightarrow x=\dfrac{-5\pm \sqrt{25-4\left( 4\times \left( -6 \right) \right)}}{2\times 4}\]
Now we will perform basic arithmetic multiplication and the equation will be reduced to \[\Rightarrow \]\[x=\dfrac{-5\pm \sqrt{25-\left( -96 \right)}}{2\times 4}\]
Here we will transform the equation by using basic arithmetic simplification of addition and equation will be transformed into
\[\Rightarrow x=\dfrac{-5\pm \sqrt{121}}{8}\]
Now we perform the basic application of square root and reduce the given equation into
\[\Rightarrow x=\dfrac{-5\pm 11}{8}\]
And now we solve the equation by using simple arithmetic division and addition and we get
\[\Rightarrow x=-2,\dfrac{3}{4}\]
Therefore we can conclude that the value of \[x\] in \[4{{x}^{2}}+5x-6=0\] is \[x=-2,\dfrac{3}{4}\].
Note: We should be very peculiar with our calculations while solving the quadratic equations with simple basic concepts of arithmetic simplifications and transformations. Similarly questions of these kind quadratic equations can be solved by using the basic formula of \[\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}\] which are the roots of the given quadratic equation. This question can also be solved using factorization but here we have been asked to use the quadratic formula. The solution using factorisation will be as follows $4{{x}^{2}}+5x-6=0\Rightarrow 4{{x}^{2}}-3x+8x-6=0\Rightarrow \left( x+2 \right)\left( 4x-3 \right)=0\Rightarrow x=-2,\dfrac{3}{4}$ .
Complete step-by-step answer:
Now considering the question in which we are asked to solve the given equation \[4{{x}^{2}}+5x-6=0\] and derive the value of the unknown variable \[x\].
Firstly, we will observe the given equation carefully and compare the given quadratic equation with the basic quadratic equation \[a{{x}^{2}}+bx+c=0\].
By comparing the given quadratic equation \[4{{x}^{2}}+5x-6=0\] with the basic quadratic equation \[a{{x}^{2}}+bx+c=0\] , we get,
\[\Rightarrow a=4,b=5,c=-6\]
Here in the question the variable x is nothing but the roots of the given equation \[4{{x}^{2}}+5x-6=0\] .
We can find the roots of the quadratic equation by basic formula \[x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}\] . After comparing the given quadratic equation with the basic equation we substitute them and we get,
\[\Rightarrow x=\dfrac{-5\pm \sqrt{25-4\left( 4\times \left( -6 \right) \right)}}{2\times 4}\]
Now we will perform basic arithmetic multiplication and the equation will be reduced to \[\Rightarrow \]\[x=\dfrac{-5\pm \sqrt{25-\left( -96 \right)}}{2\times 4}\]
Here we will transform the equation by using basic arithmetic simplification of addition and equation will be transformed into
\[\Rightarrow x=\dfrac{-5\pm \sqrt{121}}{8}\]
Now we perform the basic application of square root and reduce the given equation into
\[\Rightarrow x=\dfrac{-5\pm 11}{8}\]
And now we solve the equation by using simple arithmetic division and addition and we get
\[\Rightarrow x=-2,\dfrac{3}{4}\]
Therefore we can conclude that the value of \[x\] in \[4{{x}^{2}}+5x-6=0\] is \[x=-2,\dfrac{3}{4}\].
Note: We should be very peculiar with our calculations while solving the quadratic equations with simple basic concepts of arithmetic simplifications and transformations. Similarly questions of these kind quadratic equations can be solved by using the basic formula of \[\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}\] which are the roots of the given quadratic equation. This question can also be solved using factorization but here we have been asked to use the quadratic formula. The solution using factorisation will be as follows $4{{x}^{2}}+5x-6=0\Rightarrow 4{{x}^{2}}-3x+8x-6=0\Rightarrow \left( x+2 \right)\left( 4x-3 \right)=0\Rightarrow x=-2,\dfrac{3}{4}$ .
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.